Complete plastome sequence of Croton laevigatus Vahl (Euphorbiaceae): an endemic species in Hainan, China. Issue 1 (2nd January 2020) - Liao, Xin; Wang, Hong-Xin; Zhu, Zhi-Xin; Wang, Hua-Feng
Abstract: Croton laevigatus grows as an evergreen tree or shrub with 15 meters height. It is distributed in the dense or open forests of Hainan province, China. Here, we report and characterize the complete plastome of C. laevigatus in an effort to provide genomic resources useful for promoting its systematics research. The plastome of C. laevigatus is found to possess a total length 162, 515 bp with the typical quadripartite structure of angiosperms, contains two Inverted Repeats (IRs) of 26, 866 bp, a Large Single-Copy (LSC) region of 90, 234 bp and a Small Single-Copy (SSC) region of 18, 549 bp. The plastome contains 113 genes, consisting of 79 unique protein-coding genes, 30 unique tRNA genes and four unique rRNA genes. The overall A/T content in the plastome of C. laevigatus is 64.10%. The phylogenetic analysis indicated that C. laevigatus is close to C. tiglium within Euphorbiaceae in this study. The complete plastome sequence of C. laevigatus will provide a useful resource for the conservation genetics of this species as well as for the phylogenetic studies of Euphorbiaceae.